2005
DOI: 10.1055/s-2005-837798
|View full text |Cite
|
Sign up to set email alerts
|

Kombinationstherapie einer fetalen supraventrikulären Tachykardie mit Flecainid und Digoxin

Abstract: Persistent fetal supraventricular tachycardia (SVT) with more than 210 bpm frequently leads to congestive heart failure. We report on a case with SVT and congestive heart failure that converted into sinus rhythm within 19 days of therapy with flecainide and beta-acetyldigoxin. A 32-year-old II gravida I para (25 + 1 weeks of gestation) presented with fetal SVT of 267 bpm. A non-immunologic hydrops fetalis was diagnosed by ultrasound showing ascites, pleural and pericardial effusion and tricuspid regurgitation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…The problem with fetal tachyarrhythmias is the risk of hydrops fetalis and subsequent death. [52] Supraventricular tachycardias are the most common fetal tachycardias, whereas other arrhythmias are observed less frequently. An analysis of 11 studies reported from 1991 to 2002 showed a fetal SVT as the underlying arrhythmia in 73.2% and AFlut in 26.2%.…”
Section: Acute Therapy Of Fetal Arrhythmiasmentioning
confidence: 99%
See 1 more Smart Citation
“…The problem with fetal tachyarrhythmias is the risk of hydrops fetalis and subsequent death. [52] Supraventricular tachycardias are the most common fetal tachycardias, whereas other arrhythmias are observed less frequently. An analysis of 11 studies reported from 1991 to 2002 showed a fetal SVT as the underlying arrhythmia in 73.2% and AFlut in 26.2%.…”
Section: Acute Therapy Of Fetal Arrhythmiasmentioning
confidence: 99%
“…reported a 25-year-old pregnant woman with persistent fetal tachycardia (rate 267 beats/min) and subsequent hydrops fetalis. [52] The woman was treated with flecainide and digoxin, and the tachycardia converted to sinus rhythm. A few days later, no signs of fetal heart failure were present.…”
Section: Acute Therapy Of Fetal Arrhythmiasmentioning
confidence: 99%